2022
DOI: 10.3389/fcvm.2022.848091
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Cardiac Tamponade in Association With Cytokine Release Syndrome Following CAR-T Cell Therapy

Abstract: Chimeric antigen receptor T (CAR-T) cell therapy has been shown to have substantial efficacy against refractory hematopoietic malignancies. However, it frequently causes cytokine release syndrome (CRS) as a treatment-specific adverse event. Although cardiovascular events associated with CAR-T cell therapy have been increasingly reported recently, pericardial disease is a rare complication and its clinical course is not well characterized. Here, we report a case of acute pericardial effusion with cardiac tampon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…One important finding from our case report and that of Moriyama et al ( 9 ), is that both patients initially presented a pericardial localization of the lymphoma. Therefore, we should consider a pre-existing pericardial localization of the lymphoma as a major risk factor for CAR-T cell therapy-induced pericardial effusion with cardiac tamponade.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…One important finding from our case report and that of Moriyama et al ( 9 ), is that both patients initially presented a pericardial localization of the lymphoma. Therefore, we should consider a pre-existing pericardial localization of the lymphoma as a major risk factor for CAR-T cell therapy-induced pericardial effusion with cardiac tamponade.…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, cardiac tamponade in association with CRS following CAR-T cell therapy has only been reported once. Indeed, Moriyama et al ( 9 ) reported the case of a 59-year-old man with refractory DLBCL who was also treated with CAR-T cell therapy and who presented cardiac tamponade associated with grade 4 CRS. However, these authors did not perform pericardiocentesis in their patient who had severe myelosuppression and shock, which they considered a major risk factor for complications ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of CAR T cell therapy on the cardiovascular system manifests as hemodynamic compromise, myocardial injury/dysfunction, and/or cardiac arrhythmias (60, 61). There is also the potential for pericardial complications, such as in a case report (62) describing a patient with high-grade lymphoma who developed a pericardial effusion and tamponade with cardiogenic shock after CAR T therapy. Higher-grade CRS appears to be linked to adverse cardiovascular events of all types.…”
Section: Cardiovascular Complications Of Cellular Imunotherapiesmentioning
confidence: 99%